Skycrapers - City in the Clouds (Proceedings of Faculty of Civil Engineering, 2019)
The project “Skyscrapers – city in the clouds“ was initiated by a group of students and experts in architecture, landscape architecture, and design, called “Sekcija”. The project was selected by the Croatian chamber of architects as one of the eleven projects of great interest for Croatian architecture selected in 2017. The initial idea was to investigate identities, create polls on citizens’ opinions and facilitate workshops; but this idea quickly grew into a three-day festival dedicated to the city of Rijeka skyscrapers.
Keywords: Rijeka's identity; vertical housing; skyscrapers